OPTIMAL FILTRARION SIGNALS RADIOAETIMETER OF SMALL ALTITUDE WITH REGARDS POLEARIRATION - A. I. Logvin; E. A. Lutin (Научный вестник МГТУ ГА)
The article considers the possibility of improving polyrization properties of receivers for continuously frequency-modulated signals in radioaltimeter of small altitude with regards its polariazation are considered. For that Methods of Markov non-linearity filtrations are used.